Project management planning of the small house construction in samarinda using the critical path method (CPM) - Surahman, Surahma; Kusumah, Angga; Tiara, Tiara; S. Tomby, Rindayani; Nurmaulida, Nurmaulida (Institute of Computer Science (IOCS), 2024)
The house construction project was carried out in a span of 120 days involving 6 people. Data processing is carried out to ensure the smooth implementation of the project in accordance with the predetermined plan. By using the literature study method and secondary data processing, this study aims to develop an effective and efficient house construction project management plan, the method used in this project planning is the CPM critical path method (Critical path method). The project is carried out by 6 people, all materials such as sand, stone, cement and wood have been prepared in advance by the project owner. The information used in this analysis is based on direct interviews between the project owner and the researcher. Thus, the main conclusion is that effective and efficient project management, including careful budget planning and good control, is very important in ensuring the success of house construction. By maintaining a balance between time, budget, and quality, and applying the latest management techniques, the house construction project can be completed well in accordance with the set plan. The house construction project was carried out in a span of 120 days involving 6 people, with Mr. Ardiansyah in charge of project management. All materials such as sand, stone, cement, and wood have been prepared in advance by the project owner, ensuring the availability of construction materials during implementation. Normal and quick duration work network analysis is used to understand the sequence of construction activities, fastest duration, and normal duration of each project activity. By utilizing the CPM method, the critical path of the shophouse construction project can be identified to calculate the estimated project completion time and the minimum duration required.